Association of mutations in TBK1 with sporadic and familial amyotrophic lateral sclerosis and frontotemporal dementia - Freischmidt, Axel; Müller, Kathrin; Ludolph, Albert C.; Weishaupt, Jochen H.; Andersen, Peter M. (JAMA neurology, 2017)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are related neurodegenerative syndromes that occur sporadically or have been associated with mostly dominant inheritance of mutations in more than 30 genes. A critical issue is whether all reported mutations are disease causing or are coincidental findings. In this review we analyze the pathogenicity of nonsynonymous variants in the newly discovered gene encoding TANK-binding kinase 1 (TBK1). The available data suggest that mutations in TBK1 that cause a 50% reduction of TBK1 protein levels are pathogenic. In most cases, the almost complete loss of expression of the mutated TBK1 allele is due to loss-of-function mutations creating a premature termination codon and the degradation of the mutated messenger RNA by nonsense-mediated messenger RNA decay. In addition, TBK1 protein levels reduced by 50% have been proven for specific in-frame deletions of 1 or several amino acids, probably due to increased degradation of the mutated protein. Evaluation of many of the TBK1 missense mutations found in patients with ALS or FTD is prevented by missing data demonstrating cosegregation of the variants and incomplete knowledge about the TBK1 functions relevant for neurodegeneration. These findings suggest that haploinsufficiency of TBK1 is causative for ALS and FTD regardless of the type of mutation. Evaluation of TBK1 variants that do not cause haploinsufficiency is not possible without data demonstrating cosegregation.
Gesehen am 08.07.2021